Traffic Safety Benefit of A Lane Departure Warning System - Irene Isaksson-Hellman; Magdalena Lindman (International Journal of Automotive Engineering, 2018)
Lane departures can have serious consequences when resulting in run-off-road and oncoming crashes and effective countermeasures are of utmost importance. The objective of this study was to evaluate the real-world crash avoidance effectiveness of a Lane Departure Warning (LDW) crash avoidance system, introduced as optional mounted equipment in Volvo car models in 2008. Situations addressed by the LDW system—single-vehicle run-off-road and oncoming crashes in which the driver unintentionally leaves the lane without loss of control—were identified in insurance claims data. To evaluate the crash avoidance effect, crash rates were calculated and compared for vehicles with and without LDW. The rate of run-offroad crashes without traction loss was reduced by 30% if the vehicle had LDW (RD = 0.20 , 80% CI [0.03, 0.37]). There were not enough oncoming crashes to evaluate them statistically. The analysis revealed that the system has a large crash avoidance effect in real-world traffic; and the findings are promising for further refinement of these technologies, which target the avoidance of run-off-road and oncoming crashes.